INTERPRETASI STRUKTUR BAWAH PERMUKAAN GUNUNG MURIA MENGGUNAKAN ANALISA DATA GRAVITASI - Balulu, Nasrun (Jurnal Neutrino, 2011)
A geophysical survey using gravity method was carried out in Muria  volcano. This research aimed to interpret the subsurface geology condition of the research area based on gravity data analysis. Research area is (47,6 x 45) km2    with 222 observation  points. Gravitymeter  LaCoste Romberg type G-1118 MVR was used to    measure the  gravity field, and differential method of Global Positioning System (GPS) was used to measure the position and elevation.Data processing was performed to gain complete Bouguer  anomaly of both residual and  regional. Bouguer density using graphical method resulted to the value of 2.67 gr/cm3.  Transformation to a horizontal plane was performed obtain by using equivalent mass method with horizontal level’s height of 1602 meters beyond the spheroid reference and equivalent The separation of regional anomaly and residual  anomaly  was  generated  through  upward  continuation  method  and  resulted  to  regional anomaly in the height of  15000 meters up the spheroid reference. The residual anomaly acquired by subtract the regional anomaly toward the complete Bouguer anomaly in a horizontal plane.The subsurface modelling of Muria  volcano and its surrounding was acquired from  Grav2DC for Windows. The result shows that Muria volcano and its surrounding was regionally controlled by rock resulted from volcanic processes as lava (density 2,91 gr/cm3). This volcanic rock due to the gravity collapse performed a caldera filled by andesit (density 2,58 gr/cm3). Another rock which is deposited in  Muria  volcano  are  tuff  from  Muria  Tuff  (density  2,4  gr/cm3),  tuff  sandstone  from  Patiayam formation (density 2,5 gr/cm3),  limestone from Bulu formation (density 2,7 gr/cm3), and  limestone from Ngrayong formation (density 2,8 gr/cm3).Keywords:Bouguer anomaly, Regional anomaly, Residual anomaly,  Modeling, Subsurface stracture.